Interfacial Behavior of the Steel–UHPC Composite Deck With Toughened Epoxy Bonding - Chen, Jun; Leng, Jingchen; Jiang, Jinlong; Zou, Yang; Zhou, Jianting (Frontiers in Materials, 2022)
Abstract: Using traditional stud connectors to connect the UHPC layer and steel deck is detrimental to the construction speed and fatigue performance of the composite structure. Connecting the Steel-UHPC interface with toughened epoxy bonding is a potential alternative to avoid this issue. To explore whether the toughened epoxy bonding interface can reduce the amount of bridge deck studs or even cancel the studs, a numerical simulation was conducted in this paper. Non-toughened epoxy bonding interface, toughened epoxy bonding interface, few studs + toughened epoxy bonding interface, and full studs connection interface were designed respectively to study the interfacial behavior of the steel-UHPC composite deck. And the constitutive model of the toughened epoxy bonding interface is verified through the direct shear test and compression-shear test. The results show that the maximum interface shear stress of toughened epoxy bonding interface is 0.61 MPa under the standard wheel load, which is 20.78% lower than that of the non-toughened epoxy bonding interface. Under the overload, the interface failure of the toughened epoxy bonding interface is more concentrated and exhibits a smaller damage area compared with the non-toughened epoxy bonding interface. When the interface defect is 5%, the toughened epoxy bonding interface only has a few interface damage, exhibiting good defect tolerance. Compared to the traditional full studs connection interface, the interface shear stress in the few studs + toughened epoxy bonding interface is more uniform, which avoids the stress concentration in the root of studs, and the studs’ average stress is significantly reduced by 63.21%. It is verified that using the toughened epoxy bonding interface can significantly reduce the amount of studs.